2019
DOI: 10.21203/rs.2.10906/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Improved Clinical Outcome Using Transarterial Chemoembolization Combined with Radiofrequency Ablation for Patients in Barcelona Clinic Liver Cancer Stage A or B Hepatocellular Carcinoma Regardless of Tumor Size: Results of a Single-center Retrospective Case Control Study

Abstract: Background To determine the safety and efficacy of transarterial chemoembolization (TACE) combined with radiofrequency ablation (hereafter, TACE-RFA) in treating Barcelona Clinic Liver Cancer (BCLC) Stage A or B (hereafter, BCLC A/B) hepatocellular carcinoma (HCC) patients, and to explore the range of tumor sizes suitable for combination therapy. Methods This retrospective study assessed the consecutive medical records of HCC patients with BCLC A/B who received TACE-RFA or TACE from September 2009 to Septem… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
1
6
0
Order By: Relevance
“…TACE can improve survival in liver cancer patients by combining targeted chemotherapy with ischemic necrosis caused by arterial embolization [22]. However, PLA is a serious postoperative complication, which deserves our attention.…”
Section: Discussionmentioning
confidence: 99%
“…TACE can improve survival in liver cancer patients by combining targeted chemotherapy with ischemic necrosis caused by arterial embolization [22]. However, PLA is a serious postoperative complication, which deserves our attention.…”
Section: Discussionmentioning
confidence: 99%
“…e classification and diagnosis system of liver diseases based on contrastenhanced ultrasound (CEUS) imaging achieves the classification of liver diseases [23]. Some scholars have applied 2D-CEUS in the follow-up of liver cancer after surgery [24], while further development of 3D-CEUS makes imaging examination enter a new stage of microcirculation system diagnosis. is examination method can significantly enhance the echo signal of blood, which facilitates dynamic display of the blood perfusion of liver lesions.…”
Section: Discussionmentioning
confidence: 99%
“…A retrospective study conducted for nine years with a sample population of 2247 patients with HCC, BCLC stage A or B of varying sizes showed that there was overall survival and progression-free survival in patients at one, three, five, and eight years when TACE was combined with RFA than TACE alone, thereby concluding that the combination was effective regardless of the size (Table 4 ) [ 31 ]. TACE is the recommended treatment approach for intermediate stage (BCLC-B) HCC, which comprises large asymptomatic or numerous tumors with no invasion of vascular channels or extrahepatic metastasis; the intermediate stage is further classified based on tumor burden (Table 1 ) [ 24 , 26 ].…”
Section: Reviewmentioning
confidence: 99%